Case-control study on ocular changes and ophthalmic Doppler velocimetric indices among preeclamptic and normotensive pregnant women in Ibadan, Nigeria. Issue 1 (13th September 2020) - Onwudiegwu, Chiemelie; Adekanmi, Ademola; Olusanya, Bolutife; Lawal, Olatunji; Adedokun, Babatunde; Morhason-Bello, Imran; Oladokun, Adesina
Abstract : Objective: To compare the ocular changes and Doppler velocimetric indices in preeclamptic and normotensive pregnant women. Methods and analysis: This was a case-control study of 71 preeclamptic women and 72 parity-matched normotensive pregnant women conducted at the University College Hospital, Ibadan, Nigeria. Demographic data were obtained using questionnaires. All participants had visual acuity assessment, funduscopy, intraocular pressure measurement and orbital Doppler ultrasonography. The differences in parameters between the two groups were tested using Student's t-test for quantitative variables and χ 2 tests for categorical variables. Results: There were no significant differences between cases and controls with respect to sociodemographic variables. The mean pulsatility index was 1.35±0.46 in cases and 2.1±0.4 in controls (p<0.001); the resistivity index was 0.7±0.18 in cases and 0.83±0.27 among the controls (p=0.01). A similar pattern was observed in the peak systolic velocity (p<0.001) and the peak ratio (p<0.001). There was no significant difference between the groups concerning end-diastolic velocity (p=0.535). Three preeclampsia patients (5.2%) had abnormalities on funduscopy compared with none of the controls. Preeclamptic women had significantly higher intraocular pressures in both eyes at baseline and at 24 hours post delivery. Conclusion: This study demonstrated lower Doppler velocimetry and impedance parameters and higher intraocular pressure among preeclampsia cases compared with controls. Abnormal funduscopic findings were observed in a few preeclamptic women and none among the controls. Ophthalmic artery Doppler parameters could be useful in identifying those women who are likely to suffer preeclampsia and its complications.